2009
DOI: 10.1211/jpp.61.03.0014
|View full text |Cite
|
Sign up to set email alerts
|

Active absorption of ginsenoside Rg1 in vitro and in vivo: the role of sodium-dependent glucose co-transporter 1

Abstract: The data suggested that adrenaline enhanced the absorption of Rg1 by regulating sodium-dependent glucose co-transporter 1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“… 28 30 Caco-2 cells are known to express active transporters, including sugar transporters, such as SGLT1, GLUT2, and GLUT5. 10 A study by Liu et al also reported that a sugar transporter, SGLT1, is responsible for the transport of glycosides in Caco-2 cells. 31 Analyzing our permeability assay data with the literature reports in mind, it can be interpreted that the glycosylated flavonoids assessed here may be actively transported, possibly by sugar transporters across Caco-2 monolayers.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“… 28 30 Caco-2 cells are known to express active transporters, including sugar transporters, such as SGLT1, GLUT2, and GLUT5. 10 A study by Liu et al also reported that a sugar transporter, SGLT1, is responsible for the transport of glycosides in Caco-2 cells. 31 Analyzing our permeability assay data with the literature reports in mind, it can be interpreted that the glycosylated flavonoids assessed here may be actively transported, possibly by sugar transporters across Caco-2 monolayers.…”
Section: Resultsmentioning
confidence: 98%
“…These saponins are actively transported by suitable transport proteins, such as sugar transporters, or can be effluxed across the monolayers by efflux pumps such as P-gp and MRP-2. 10 , 32 36 We know that Caco-2 cells express active transporters including sugar transporters such as SGLT1 (responsible for the transport of glycosides), 31 GLUT2 and GLUT5. 10 Analysis of our permeability assay data in light of these literature reports suggests that the glycosylated saponins assessed here may be actively transported by sugar transporters across Caco-2 monolayers.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, both in vitro and in vivo studies have shown that the transport of ginsenoside Rb1 across the blood-brain barrier was mediated by glucose transporter 1 (GLUT1) 28. Similarly, a previous study revealed that ginsenoside Rg1 was actively transported via sodium-coupled glucose co-transporter 1 (SGLT1) into the intestine 29. Thus, ginsenoside has the potential to work as an active targeting ligand to facilitate the accumulation of drug-loading liposomes at the tumor site via interaction with the GLUT of tumor cells.…”
Section: Introductionmentioning
confidence: 99%